The Lord's Prayer - O'Neill, J. C. (Journal for the study of the New Testament, 1993)
The Lord's Prayer in Matthew and the Didache is actually a collection of prayers of Jesus, each of which originally had a separate existence. The first prayer in the collection was taught to the disciples, and the rest were remembered from the short prayers Jesus appended to the set daily prayers observed by him and his disciples. The Lord's Prayer in Luke is a similar independent collection of these prayers, except that the first prayer, 'Father, let your Holy Spirit come and cleanse us', was originally given in response to a request, 'Lord, teach us to pray as John taught his disciples'. Each prayer is expounded in turn. The petition for bread has suffered corruption. The petition on forgiveness is two prayers wrongly combined. New evidence is produced to support Torrey's reading of the petition on temptation.